A Community Resilience Framework for community development practitioners building equity and adaptive capacity. Issue 2 (15th March 2019) - Cafer, Anne; Green, John; Goreham, Gary
ABSTRACT: This article combined the Sustainable Livelihoods Approach and Community Capitals Framework to address four critical concerns in the current community resilience literature. One concern is the need for greater flexibility to account for the wide variety of actors within a community system. A second concern––the dominance of only four major outcomes (nutrition security, food security, environmental sustainability, and economic security)––ignores other important system-level capacities. A third concern in the literature is the normative discourse within resilience. The fourth concern with the state of the literature is overemphasis on specific resilience rather than general resilience. To address these issues, the Community Resilience Framework was developed with a particular emphasis on community development practice. This article also provides an introduction to two potential methodologies that can be paired with the framework to engage communities, inform policy, and build resilience.